GenBank 2023 update. Issue Volume 51:Issue D1(2023) (9th November 2022) - Sayers, Eric W; Cavanaugh, Mark; Clark, Karen; Pruitt, Kim D; Sherry, Stephen T; Yankie, Linda; Karsch-Mizrachi, Ilene
Abstract: GenBank ® (https://www.ncbi.nlm.nih.gov/genbank/ ) is a comprehensive, public database that contains 19.6 trillion base pairs from over 2.9 billion nucleotide sequences for 504 000 formally described species. Daily data exchange with the European Nucleotide Archive (ENA) and the DNA Data Bank of Japan (DDBJ) ensures worldwide coverage. Recent updates include resources for data from the SARS-CoV-2 virus, NCBI Datasets, BLAST ClusteredNR, the Submission Portal, table2asn, a Foreign Contamination Screening tool and BioSample.